Study on the Effect of Oxygenated Fuels on Emissions Characteristics: A Comparative Study between Compression Ignition and Spark Ignition Engines - L. Siwale; R. J. Kashinga; S. Chama; J. Siame; A. Bereczky (New Innovations in Chemistry and Biochemistry Vol. 3, 2021)
It is widely argued that use of petroleum is one of the biggest contributors to environment degradation. In this study, burning of oxygenated fuel blends in diesel and gasoline engines is investigated with particular attention to emissions. The study focus was twofold; firstly, to determine the extent by which emissions of NOx, uHC and CO are increased or reduced for various loads in BMEP. And secondly to compare the emissions between the two engines. In the gasoline engine, 20% methanol was blended with 80% gasoline (M20), while a blend of 20% n-butanol and 80% diesel (B20) was considered in the diesel engine. The gasoline engine was a naturally aspirated Suzuki RS-416 1.6L engine type and the diesel engine was a 1Z type, 1.9L Turbo-Direct injection (TDI). Results showed that NOx emissions increased with an increasing brake mean effective pressure (BMEP) for diesel fuel (DF) but was slightly lower than the blend B20 at 50 and 75% load; whereas using M20, NOx reduced in reference to gasoline fuel (GF) but was four times higher than that obtained in diesel engine. Firing B20 diminished the quality of unburned hydrocarbons (uHC) emissions in diesel engine based on the reference fuel DF. The range of emissions of uHC however was far less in the diesel engine than in the gasoline engine: 10-60 ppm and 600 to 700 ppm respectively. M20 reduced uHc concentration more than the GF above 25% BMEP. The concentration of carbon monoxide (CO) increased more for M20 than GF. Similarly, emission concentration of CO in B20 increased relative to DF. Exhaust gases temperature (EGT) was lower for all oxygenated blends, M20 and B20, than for GF and DF.